ANALYSIS ON THE EXTERNAL FACTORS AFFECTING PRODUCT INNOVATION FOR MARKETING PERFORMANCE DEVELOPMENT (A Case Study on PT. TELKOM Indonesia Central Java & Yogyakarta) - Stefani prima Dias Kristina; Bambang Purwanggono (Industrial Engineering Online Journal, 2012)
ABSTRACT Complexity and challenges a company faces require it to have an accurate innovation strategy so that it can compete with its competitors. PT. Telkom Indonesia is one of companies that have many competitors. Therefore, PT. Telkom must be able to survive by continually making innovations so that Telkom can keep controlling the market with the innovations made. However, a problem occurs that there is no significant improvement in the number of customers from some of PT. Telkom products. Meanwhile, the sales volume will depend on the number of customers whose average consumption level has been known to be constant. Due to this problem, a research was conducted to know to what extent the influence of customer, competitor, and technology orientations was towards product innovation in PT. Telkom so that recommendations and betterment steps could be given to improve the marketing performance. This research used Structural Equation Modeling (SEM) method. The SEM data processing results using AMOS 20 software for full model had fulfilled goodness of fit criteria as follows: chi square = 477,638; probability = 0; GFI = 0,786; AGFI = 0,743; CFI = 0,879; TLI = 0,865; RMSEA = 0,071; CMIN/DF = 1,636. Furthermore, it was also gained that competitor orientation was the most influencing variable towards product innovation as seen from its result that was as much as 42%. Meanwhile, the influence of technology and customer orientations was as much as 22,6% and 21,9%.